The Impact of National Culture on Sustainability Reporting: A Cross Country Analysis - Yamen, Ahmed; Nimer, Khalil; Ramadan , Abdulhadi; Abidi, Oualid (Asian Journal of Empirical Research, 2018)
This study investigates the influence of culture on governance, social and environmental sustainability across 59 countries. Hofstede’s culture dimensions have been used as a measure of culture, RobecoSAM sustainability measure is used as a proxy for governance, social and environmental sustainability reporting. The results reveal the countries that are characterized by high power distance, masculinity, low individualism and long-term orientation are supposed to be less interested in sustainability reporting. To increase the sustainability reporting, it is essential for the government and decision-makers to give more focus to the culture as an important driver of sustainability.